SURVEY METODE FUSI INFORMASI UNTUK PERANCANGAN COGNITIVE PROCESSOR - Catherine Olivia Sereati; Arwin Datumaya Wahyudi Sumari (Universitas Widyatama, 2014)
Cognitive Processor is a processor which have ability to emulate how human brain work to process information by gathering information from the environment and take the inference from the information that have received. To design Cognitive processor, appropriate methode is need to support the performance of this processor. Knowledge Growing System (KGS) is a new development of Artificial Intelligence that have ability to growing knowledge base on information which have been gathered as time passes. KGS concept emerge by observing mechanism of human brain when doing information fusion to gain new knowldege. This paper aimed to discuss several fusion information method as a basis to design Cognitive Processor.